Pengaruh Biaya Bahan Baku dan Biaya Tenaga Kerja Langsung Terhadap Penjualan PT Mandom Indonesia Tbk. Periode 2018—2024 - Puspita, Windi Ayu; Mulyana, Asep; Lesmana, Kusnadi Kibet; Wardhana , Didin; Priatna, Ami (Prodi Bisnis Digital Universitas Pahlawan Tuanku Tambusai, 2025)
Abstract This study focuses on the sales decline experienced by PT Mandom Indonesia Tbk (TCID) in 2024, which coincided with an increase in raw material expenses. The research aims to evaluate the extent of raw material costs, direct labor expenses, and net sales of PT Mandom Indonesia Tbk throughout the 2018–2024 period. Additionally, the study seeks to analyze the individual (partial) and combined (simultaneous) effects of raw material and direct labor costs on sales outcomes. The dependent variable in this analysis is net sales. Data were analyzed using SPSS version 25, with the company’s financial statements from 2018 to 2024 serving as the data source. A quantitative research design was adopted, employing both descriptive and associative approaches, along with multiple linear regression analysis. The results of hypothesis testing indicate that neither raw material costs nor direct labor expenses significantly affect sales when examined independently. However, when evaluated together, both variables have a statistically significant impact on sales performance.